Geologic controls on the Muara Laboh geothermal system, Sumatra, Indonesia - Stimac, Jim; Schmitt, Axel Karl (Geothermics, 2019)
An integrated review of the stratigraphy and alteration of the Muara Laboh geothermal system suggests that sector collapse and subsequent erosion of the Patah Sembilan volcano may be responsible for significant changes in permeability and fluid circulation during its evolution. This sector collapse is relatively old, probably occurring more than 41,000 years ago. It is likely that unroofing of part of the clay cap of the system due to edifice collapse and subsequent erosion, resulted in extensive boiling, fluid loss, and precipitation of quartz, calcite, and other minerals that reduced permeability in the upper part of the SW reservoir. Vein paragenesis and fluid inclusion data show that the geothermal system was hotter and more saline in the past. Cooling is most pronounced in the shallow NE sector. Conversely the SW reservoir is currently close to fluid inclusions temperatures but has significantly lower salinity, indicating an increased fraction of meteoric recharge. The reservoir section includes a wide variety of volcanic and intrusive rocks ranging in age from <0.5 to 96 Ma. The NE reservoir is hosted mainly in the lower part of the Patah Sembilan Andesite and underlying Upper Silicic Formation, whereas the SW reservoir is hosted by an underlying intrusive complex. At least two episodes of intrusion, in the Cretaceous and Miocene were dated. These intrusions are probably hosted by Miocene and Early Tertiary to Mesozoic age volcanics of andesitic to basaltic composition. Late-stage dikes, inferred from cuttings and image logs, may provide an indication of more recent intrusion.
Gesehen am 09.10.2019